Efektivitas Strategi Pemasaran dalam Pembiayaan Cicil Emas di Bank Syariah Indonesia KC Bojonegoro - rahayuningsih, eka; Muttaqin, M Khoirul; Styawati, Endang (Institut Agama Islam Negeri Kendari, 2026)
This study aims to analyze the effectiveness of marketing strategies in gold installment financing to increase public interest in using Islamic financing products. The method used in this research approach is qualitative with a descriptive research type. Data sources include both primary and secondary data sources. Data collection techniques utilized interviews and documentation. Analysis techniques included data collection, data reduction, data presentation, and conclusion drawing. The results show that the marketing strategy using the 7Ps marketing mix theory—comprising Product, Price, Place, Promotion, People, Process, and Physical Evidence—has a significant impact on customer satisfaction and interest in using the gold installment product. This study provides recommendations for Bank Syariah Indonesia KC Bojonegoro to enhance the effectiveness of its marketing strategies in the future. The novelty of this research lies in its object of study, namely gold installment products in Islamic banking, which remain relatively under-researched compared to other financing products. This study also positions customer satisfaction and product usage interest as vital variables in assessing the effectiveness of Islamic marketing strategies in the modern financial industry competition era.